2018
DOI: 10.1038/s41598-018-21882-0
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of cell associated antiretroviral drug concentrations with a novel RPP30 droplet digital PCR assay

Abstract: Quantification of antiretroviral (ARV) drug concentrations in peripheral blood mononuclear cells (PBMCs) and tissue isolated mononuclear cells (TIMCs) from lymph node (LNMC) and rectum (RMC) is an important measure of bio-distribution. Normalization of drug concentrations is critical to represent tissue drug concentrations and to analyze both intra-individual and inter-individual variability in drug distribution. However, a molecular method to normalize intracellular drug concentrations in PBMCs and TIMCs meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
(51 reference statements)
1
33
0
1
Order By: Relevance
“…Further, we explored the specific modification functions of RPP30 at each stage of gene expression. Consistent with previous research findings, we found that RPP30 was involved in the modification of RNA, not DNA, in both tumor and non-tumor samples [ 14 , 15 , 18 ]. Surprisingly, we found that RPP30 was closely related to protein modification in non-tumor brain samples, but not in primary GBM samples in both the CGGA and TCGA databases ( Figure 2C ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Further, we explored the specific modification functions of RPP30 at each stage of gene expression. Consistent with previous research findings, we found that RPP30 was involved in the modification of RNA, not DNA, in both tumor and non-tumor samples [ 14 , 15 , 18 ]. Surprisingly, we found that RPP30 was closely related to protein modification in non-tumor brain samples, but not in primary GBM samples in both the CGGA and TCGA databases ( Figure 2C ).…”
Section: Resultssupporting
confidence: 92%
“…RNase P is also known as RNA polymerase III and is one of three major nuclear RNA polymerases in human cells. Studies have shown that in addition to the modification of tRNA, RNase P is involved in the regulation of gene transcription and cell cycle [ 14 , 15 ]. Previous work has reported that RPP30 plays a role in tumorigenesis and malignant progression in breast, ovarian, and lung cancers [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…PHHs were treated with rifampin, rifabutin and rifapentine at 10 µM concentration for 72 h. with the corresponding untreated (negative) and 0.0025% methanol (vehicle) treated controls. We measured intracellular concentrations (ICC) of parent and des-acetyl-metabolites by liquid chromatography tandem mass spectroscopy (LC-MS/MS) as we have previously described [45][46][47][48][49] .…”
Section: Materials and Methods Primary Human Hepatocytes (Phhs)mentioning
confidence: 99%
“…After 40 cycles, an extension step was performed at 72°C for 10 minute and a final step of DNA polymerase deactivation step at 95°C for 5 min. FC in mRNA expression level of each sample was determined using ΔΔCT method 74 and GAPDH was used as internal control in qPCR assays. Three minimum replicates were used for all samples in qPCR assays (n = 3).…”
Section: Methodsmentioning
confidence: 99%